Gamification’s effect on learning and engagement in programming course among non-major computer science students. - Md. Noor, Norah (Penerbit UTM Press, 2022)
In this quasi-experimental research design with non-equivalent groups, the gamification method was used in the teaching delivery of a computer programming course among non-major computer science students. The gamification technique incorporates all game elements, including points, leaderboards, obstacles, and badges. We contrasted the gamified course (Section 02) with its non-gamified equivalent to determine how gamification impacts learner engagement and performance (Section 01). The experiment was conducted among first-year students in one public university's Pre-Service Teacher programme during the second half of the first semester of the academic year 2019–2020. Although there was no discernible difference in academic achievement between the experimental and control groups, the engagement results were encouraging, and students gave them positive feedback.